A comparison of the interaural time sensitivity of neurons in the inferior colliculus and thalamus of the unanesthetized rabbit - Stanford, TR (J Neurosci, 1992)
The localization of low-frequency sounds (less than 3 kHz) along the azimuth involves comparing the ongoing difference in the time of arrival of a sound at the two ears. Information about interaural time differences (ITDs) is derived from an initial comparison performed in the superior olivary complex. However, little is known about which aspects of this information are transformed as it ascends the brainstem. To address this issue, we compared the ITD sensitivity of neurons in the inferior colliculus (IC) and auditory thalamus, successive stations in the auditory pathway. We found ITD sensitivity in the IC and thalamus to be similar in several respects. At both levels, the large majority of neurons responded maximally to ITDs within the range that a rabbit would normally encounter (+/- 300 microseconds) and preferred ipsilateral delays, delays that would be created by sounds in the contralateral sound field. The range of frequencies over which ITD sensitivity was expressed was also similar in the midbrain and thalamus. Several differences were also apparent. In comparison to IC neurons, neurons in the thalamus responded over more restricted ranges of ITD, responded at lower rates, and, in response to monaural stimulation, showed an increased influence of inhibition. Finally, a greater proportion of thalamic units had characteristic delays corresponding to intermediate discharge rates. The preservation of a bias for ipsilateral delays from IC to thalamus suggests that a representation of contralateral azimuths is present at both levels. Similarities between the two levels suggest that information about ITDs is faithfully transmitted from midbrain to thalamus. Differences in ITD sensitivity, such as the sharper tuning for ITDs, suggest that the thalamus is not a simple relay. Enhanced sensitivity to ITDs should translate to better-defined azimuthal receptive fields, and therefore may be a step toward achieving an optimal representation of azimuth within the auditory pathway.